Go Further, Together : CLC 2024 Conference - Leading English Education and Resource Network (LEARN) (2024)

Wellness Innovation Lab - Variantzas, Bobbie (QUESCREN Education and Vitality Forum 2023, 2023)

New CDA Orientation Guide - Leading English Education and Resource Network (LEARN) (2023)

Wellness Innovation Lab : Workshop Guidebook - Leading English Education and Resource Network (LEARN); Percolab Coop (2023)

Étude du programme de tutorat en ligne LEARN : État récapitulatif et analyse du sondage réalisé auprès des parents de LEARN - LaBonte, Randy (Canadian eLearning Network (CANeLearn), 2023)

LEARN Online Tutoring Program Study : Summary Report and Analysis of the LEARN Parent Survey - LaBonte, Randy (Canadian eLearning Network (CANeLearn), 2023)
LEARN (Leading English Education and Resource Network) is a non-profit educational organization with a mandate to serve the English-speaking community of Quebec by offering resources and services at no charge to elementary and secondary level students. One of the rapidly growing services is online tutoring and homework. Tutors are fully qualified Quebec teachers, experienced in tutoring, working directly with elementary (gr. 2 and up) and secondary students and their families. LEARN is anticipating up to 45,000 tutorial sessions this year, almost triple the number of sessions in the 2019-2020 school year, with 200 part-time tutors involved in the service. In January 2023, LEARN mandated the Canadian eLearning Network (CANeLearn.net) to conduct an independent assessment of the program. CANeLearn sought the input of parents with children in the program to help determine how LEARN’s online tutoring met parent’s needs and how the program might be improved. A survey was developed and administered by CANeLearn, though LEARN distributed the survey in both English and French to parents of children involved in the tutoring program. The results were directly collected and used by CANeLearn to create this report about the program’s effectiveness and to analyze the tutoring program’s impact on student learning success, motivation, and confidence. Survey results were also reviewed in the context of recent research on tutoring and a discussion of findings can be found at the end of this report

LEARN Online Tutoring Program Study : Parent Survey Results and Analysis - LaBonte, Randy (2023)

Bilan annuel : CSC - Plan d'action 2023-2024 - Leading English Education and Resource Network (LEARN) (2023)

[Interviews with Community Learning Centres Staff : Key Takeaways] - Leading English Education and Resource Network (LEARN) (2023)

Learning Landscapes Journal : Education in a Pivotal Time : The Moment for Inspiration, Innovation, and Change - Leading English Education and Resource Network (LEARN) (2023)

Community Learning Centres : Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2022)

Community Learning Centres : Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2022)

New CDA Orientation Guide - Leading English Education and Resource Network (LEARN) (2022)

Roles and Responsibilities : CLC Team Members, School Boards and LEARN's Provincial Resource Team - Leading English Education and Resource Network (LEARN) (2022)

Roles and Responsibilities : CLC Team Members, School Boards and LEARN's Provincial Resource Team - Leading English Education and Resource Network (LEARN) (2022)

ArtistsInspire Grants COVID-19 Protocol - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Elementary School Workshop Catalogue : 2022-2023 School Year - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

High School Workshop Catalogue : 2022-2023 School Year - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Arts-Based Performances, Perspectives, and Approaches in Research and Pedagogy - Leading English Education and Resource Network (LEARN) (2022)

[Centres scolaires communautaires : Fiche d'information] - Leading English Education and Resource Network (LEARN) (2022)

[Centres scolaires communautaires : Fiche d'information] - Leading English Education and Resource Network (LEARN) (2022)

Le réseau des écoles communautaires du Québec - Leading English Education and Resource Network (LEARN) (2022)
Keywords: Official Language Minority Community (OLMC)

School Community Asset Map : Toolkit - Leading English Education and Resource Network (LEARN) (2022)

QUESCREN's Education Research Briefs - Horrocks, Debbie; Legault, Emma (Education and Vitality Forum, 2021)

Quebec Online Alliance (QOA) - the Online Campus for Students with Medical Exemptions from the English School Boards Across Quebec Officially Opened this Week - Leading English Education and Resource Network (LEARN) (2021)

QCGN Asks Minister Roberge to Fund LEARN to Tutor English-speaking Students - Quebec Community Groups Network (QCGN) (2021)

[Community Learning Centres : Information Sheet] - Leading English Education and Resource Network (LEARN) (2021)

Pedagogical Practices: The How of Teaching and Learning - Leading English Education and Resource Network (LEARN) (2021)

Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2021)
Keywords: Official Language Minority Community (OLMC)

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

A Principal's Guide to CLC - Leading English Education and Resource Network (LEARN) (2020)

[Community Learning Centres : Information Sheet] - Leading English Education and Resource Network (LEARN) (2020)

Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2020)

The Role for Performances in Educational Practices - Leading English Education and Resource Network (LEARN) (2020)

Bright Beginnings Project Descriptions - Community Health and Social Services Network (CHSSN) (2019)

ELAN (English-Language Arts Network) est heureux d’annoncer le lancement du programme de subventions Artistes Inspire (AI), soit un investissement de 2,2 millions de dollars destiné à créer des activités artistiques et culturelles dans les écoles de langue officielle en situation minoritaire au Québec - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

ELAN launches ArtistsInspire Grants (AIG), a $2.2 Million Investment for Quebec Official-language Minority Schools to Create Arts and Cultural Opportunities - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

Community Learning Centres Models at a Glance - Leading English Education and Resource Network (LEARN) (2019)

Annual Funding from 2019-2023 : Artists Inspire Grants - English Language Arts Network (ELAN) (2019)
Support for Schools and Artists from Quebec's English-speaking communities to connect through hands-on creative experiences an ELAN/LEARN partnership funded by the Government of Canada's Action Plan for Official Languages

A Practitioner's Guide to CLC Extension - Leading English Education and Resource Network (LEARN) (2019)

Indicators Toolkit - Leading English Education and Resource Network (LEARN) (2019)

Indicators Toolkit : Guidelines for Selection Indicators and How to Monitor Them in the Short, Medium and Long-Term - Leading English Education and Resource Network (LEARN) (2019)

Understanding Ways of Knowing : Insights and Illustrations - Leading English Education and Resource Network (LEARN) (2019)

QCGN Community Leadership Awards - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Request for Proposals: Communications Specialist to Develop Outreach Plans & Tools to Promote Micro Grants Program for Arts & Culture in English Schools in Quebec - English Language Arts Network (ELAN) (2018)

CLC Extended Model : Learnings & Next Steps from the First 4 Years - Estuaries Learning Consulting Group (Leading English Education and Resource Network (LEARN), 2018)

CLC Extended Model : Learnings & Next Steps from the First 4 Years - Estuaries Learning Consulting Group (Leading English Education and Resource Network (LEARN), 2018)
From January to March of 2018, LEARN undertook an evaluation of the CLC extended model that looked to answer two key questions: 1) Has the CLC extended model been a success, and; 2) What best practices can schools and school boards adopt to effectively introduce the CLC extended model? In asking these questions, LEARN was looking to support two specific types of stakeholders: 1) Schools and school boards wanting to understand the benefits and outcomes of the extended model; and, 2) Schools and school boards wanting a deeper understanding of how to extend effectively. The majority of school boards currently have CLCs that have been extended models for a short duration. The data presented here reflects this, as it responds to question two more fully. It will be useful to do a further evaluation in a few years’ time to gather more precise data on the success of the model, once schools have engaged with it for a longer period.

[CLC Health & Wellbeing Pathway Template] - Leading English Education and Resource Network (LEARN) (2018)

Teaching and Learning with Stories - Leading English Education and Resource Network (LEARN) (2018)

Annual Activity Report : June 1, 2016 - May 31, 2017 - Literacy Quebec (LQ) (2017)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once via conference call for professional development and networking opportunities. Through a PACTE funded project, Literacy Quebec was able to develop tools to strengthen its network. The project allowed us to examine new ways of promoting literacy and explaining the issues surrounding low literacy to the general public. The project also enabled the organization to engage more volunteers and pilot a database to track volunteers, supporters, members, etc.

The CLC Guidebook : Steps to Development - Smith, William J.; Leading English Education and Resource Network (LEARN) (2017)

Fostering Health and Well-Being in Education - Leading English Education and Resource Network (LEARN) (2017)

Teaching With Technology : Pedagogical Possibilities and Practicalities - Leading English Education and Resource Network (LEARN) (2017)

The Community Learning Centre Initiative : Framework for Action - Smith, William J. (Leading English Education and Resource Network (LEARN), 2016)
In the province of Quebec, English language-minority communities do not always have equitable access to education, health and/or social services. This challenge is particularly acute for English educational institutions and communities, especially in those regions where Anglophones make up a small percentage of the total population and the English school is the only English- language public sector institution in the community. The Community Learning Centre (CLC) Initiative helps to address this gap by building partnerships between English schools and organizations/institutions in their communities. These partnerships, facilitated by a Community Development Agent (CDA), leverage resources that benefit students, their families and the broader community. Recognizing the value of the CLC Initiative, the Association of Directors General of English School Boards of Québec (ADGESBQ) has supported its development since its inception.

Artful Inquiry : Transforming Understanding Through Creative Engagement - Leading English Education and Resource Network (LEARN) (2016)

Sustaining Impact in CLC Schools and Communities : Provincial Resource Team Report : 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Action Framework : Supporting the Well-Being of Minority English-Language Youth, Schools and Communities - Community Health and Social Services Network (CHSSN) (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

Building School-Community Partnerships : Together We can Make a Difference : CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)

Professional Development in Education : Pushing the Boundaries of Possibility - Leading English Education and Resource Network (LEARN) (2015)

Teacher Research : Integrating Action, Observation, and Reflection - Leading English Education and Resource Network (LEARN) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

Community Learning Centres : Changing Lives and Communities : 2013-2014 Annual Report of CLC Activities : September 2014 - Leading English Education and Resource Network (LEARN) (2014)

Centennial CLC Year 3 Evaluation : Taggin' Our Success! - Elston, Cindy (Leading English Education and Resource Network (LEARN), 2014)
Welcome to Centennial’s Community Learning Centre (CLC) Year 3 evaluation report! In these pages you will find highlights of an evaluation carried out between January-May of 2014. We looked at outcomes of key programs and how they relate to achieving our overall mission and mandate. We designed questions using our Theory of Change (ToC), which has six result areas including the two we focused on this year, Student Success and Community Engagement.

Inclusive Education : Socially Just Perspectives and Practices - Leading English Education and Resource Network (LEARN) (2014)

Community Learning Centres : Changing Lives and Communities : Annual Report of Activities : September 2013 - Leading English Education and Resource Network (LEARN) (2013)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2013)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2013)

Early Childhood Education : Successes and Challenges - Leading English Education and Resource Network (LEARN) (2013)

Teaching and Learning in the Digital World : Possibilities and Challenges - Leading English Education and Resource Network (LEARN) (2013)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2012)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2012)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2012)

Creativity : Insights, Directions, and Possibilities - Leading English Education and Resource Network (LEARN) (2012)

Informal Learning : Flexible Contexts and Diverse Dimensions - Leading English Education and Resource Network (LEARN) (2012)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2011)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2011)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2011)

Inquiry : Perspectives, Processes and Possibilities - Leading English Education and Resource Network (LEARN) (2011)

Mind, Brain, and Education : Implications for Educators - Leading English Education and Resource Network (LEARN) (2011)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2010)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2010)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2010)

Perspectives on Education : Voices of Eminent Canadians - Leading English Education and Resource Network (LEARN) (2010)

Poetry and Education : Possibilities and Practices - Leading English Education and Resource Network (LEARN) (2010)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2009)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2009)

Curriculum : Issues and Innovations - Leading English Education and Resource Network (LEARN) (2009)

Literacy : Multiple Perspectives and Practices - Leading English Education and Resource Network (LEARN) (2009)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2008)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2008)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2008)

Education and the Arts : Blurring Boundaries and Creating Spaces - Leading English Education and Resource Network (LEARN) (2008)

Leadership in an Era of Change - Leading English Education and Resource Network (LEARN) (2008)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2007)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2007)

Student Engagement in the 21st Century - Leading English Education and Resource Network (LEARN) (2007)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2006)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2006)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2006)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2005)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2005)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2005)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2004)

[CLC Plan Template] - Leading English Education and Resource Network (LEARN)

Creating Supportive Home Learning Environments for Children - Leading English Education and Resource Network (LEARN)

From Involvement to Engagement - Leading English Education and Resource Network (LEARN)

Fun with Families - Leading English Education and Resource Network (LEARN)

Guide to Planning and Hosting Your Community Learning Conversation - Leading English Education and Resource Network (LEARN)

The Partnership Agreement - Leading English Education and Resource Network (LEARN)

The Six Types of Family Involvement - Leading English Education and Resource Network (LEARN)

Your CLC's Operations Manual Template - Leading English Education and Resource Network (LEARN)

Your Family Makes a Difference - Leading English Education and Resource Network (LEARN)

A Guide for Caregivers - Vision Gaspé-Percé Now (VGPN)
This guide is intended for those of you who are taking care of a loved one and wish to improve the quality of life for you and your loved one. It is also intended to help you recognize the value of your work because you are enabling your loved one to live with dignity, either at home or in a facility. Anyone at any point can become a caregiver, whether it is unexpected or planner, and so the task may come about as a response to a heart-felt need or simply as the days pass. However, this means that you may offer help to a loved one without taking time to evaluate the impact it will have on your life and without realizing that your life can be completely altered.